Nutrition for Hospital Workers During a Crisis: Effect of a Plant-Based Dietary Intervention on Cardiometabolic Outcomes and Quality of Life in Healthcare Employees During the COVID-19 Pandemic. Issue 3 (May 2022) - Kahleova, Hana; Berrien-Lopez, Rickisha; Holtz, Danielle; Green, Amber; Sheinberg, Rosanne; Gujral, Harpreet; Holubkov, Richard; Barnard, Neal D.
The study tested the effects of a vegan diet on cardiometabolic outcomes and quality of life among healthcare employees during the COVID-19 pandemic. Overweight hospital employees were enrolled and randomly assigned (in a 1:1 ratio) to an intervention group, which was asked to follow a low-fat vegan diet, or a control group, asked to make no diet changes. However, due to COVID-19 disruptions, all participants remained on their usual diets from March to June (12 weeks), creating a de facto control period, and all (n = 12) started the vegan diet with online classes in June, which continued for 12 weeks. Nine participants completed all final assessments. A crossover ANOVA was used for statistical analysis of differences in cardiovascular health during the control period and during the intervention. Despite the ongoing crisis, body weight decreased (treatment effect −5.7 kg [95% CI −9.7 to −1.7]; P = .01); fasting plasma glucose decreased (−11.4 mg/dL [95% CI −18.8 to −4.1]; P = .007); total and LDL-cholesterol decreased (−30.7 mg/dL [95% CI −53.8 to −7.5]; P = .02; and −24.6 mg/dL [−44.8 to −4.3]; P = .02, respectively); diastolic blood pressure decreased (−8.5 mm Hg [95% CI −16.3 to −.7]; P = .03); and quality of life increased ( P = .005) during the intervention period, compared with the control period. A vegan diet improved cardiometabolic outcomes and quality of life in healthcare workers at the height of the COVID-19 pandemic.